Body composition and metabolic consequences of antibiotics most frequently administered to newborns in intensive care units: an experimental study in healthy newborn rats - Segura-Cervantes, Enrique; Mancilla-Ramírez, Javier; Fernández-Urrutia, Liliana; González-Gallardo, Susana; Mendoza-Gertrudis, Lourdes; Valencia-Santaella, Jasibe; Galindo-Sevilla, Norma (Frontiers in Medicine, 2024)
Introduction The increasing overuse of antibiotics in recent years has led to antibiotics being the most prescribed drugs for pediatric patients, and 72% of patients in the neonatal intensive care unit are treated with antibiotics. One effect of antibiotic use is the alteration of the microbiota, which is associated with metabolic disorders, including obesity. Methods This experimental study in newborn rats compared the administration of ampicillin/meropenem (Access/Watch groups) at 100/10 μg/g every 12 h, cefotaxime 200 μg/g every 24 h (Watch group), and amikacin 15 μg/g every 24 h (Access group) versus saline solution as the control. Each antibiotic was adjusted to the required dosages based on weight, and the doses were administered intraperitoneally daily for 5 days to 10–14 newborn male rats per group. A comparison of the morphometric and biochemical parameters registered on day 28 was performed using ANOVA. Results Amikacin had the largest effect on morphometric measurements, and low-density lipoprotein cholesterol, while cefotaxime had the largest effect on glucose and triglycerides, whereas ampicillin/meropenem produced the weakest effect on the measured parameters. Discussion The administration of antibiotics in the neonatal stage can affect the body composition of rats as well as the lipid and carbohydrate serum levels. Future studies should evaluate the toxicity of antibiotics in immature neonatal organs and could help to improve therapeutic decisions and prevent the unjustified use of antibiotics in newborns, thereby reducing metabolic consequences.